Analyzing the impact of blockchain technology on banking transaction costs using the random forest method - Ahmed, Ibrahim Elsiddig (Frontiers in Blockchain, 2025)
The rapid advancement of Blockchain technology has significantly benefited banks with more efficiency, highly secured activities, compliance, fraud prevention, and risk control. All previous studies focused on stakeholders’ perceptions and ignored measuring the value of blockchain adoption. This study addresses this gap by quantifying and rating blockchain’s impact on reducing banking transaction costs. The data has been collected from 17 of 20 United Arab Emirates national banks over 2017–2023 and analyzed using the random forest method to assess the association between blockchain adoption and four transaction cost elements. The random forest technique accurately quantifies and classifies blockchain’s role in cost reduction. The findings indicate that blockchain adoption significantly reduces processing, transfer, and fraud costs. This study has a visible practical and theoretical contribution as it shifts focus to quantifying blockchain’s impact, providing useful insights for managers, and suggesting future research across different sectors and countries.